Safety and Feasibility of Vaginal Delivery in Full-Term Pregnancy After Transvaginal-Natural Orifice Transluminal Endoscopic Surgery: A Case Series - Zhang, Shoufeng; Dong, Zhiyong; Liu, Junling; Qin, Zhenyue; Wang, Huihui; Bao, Mingyue; Wei, Weiwei; Shi, Ruxia; Chen, Jiming; Xia, Bairong (Frontiers in Surgery, 2022)
Abstract Study Objective: The aim was to investigate the outcome of vaginal delivery of full-term pregnancies in patients after transvaginal-natural orifice transluminal endoscopic surgery（vNOTES） treatment for gynecological disorders. Design: A case series report. Setting: A medical university hospital. Patients: 12 cases of successful delivery after transvaginal-natural orifice transluminal endoscopic surgery. Interventions: Long-term follow-up of patients with fertility needs after transvaginal-natural orifice transluminal endoscopic surgery. Measurements and Main Results: From 2018 to 2021, 163 cases of gynecological diseases were treated by vNOTES. One hundred forty-seven patients were followed up, with a follow-up rate of 90.1%. The average follow-up time was 28 (15-47) months, including 66 cases with fertility requirements. Among these 66 patients, 12 patients successfully got pregnant and completed delivery, including 10 cases of vaginal delivery and 2 cases of cesarean section, with no adverse pregnancy outcomes associated with vNOTES arising. Conclusion: Vaginal delivery of a full-term pregnancy after transvaginal-natural orifice transluminal endoscopic surgery appears to be safe and feasible and would not be one of the bases for elective cesarean delivery. Keywords: Transvaginal-natural orifice transluminal endoscopic surgery; Minimally invasive gynecology techniques; Transvaginal delivery; Full-term pregnancy; Childbirth ability